Functional plant traits according to pollen type in the Tajik-Uzbek Surface Data Base - Dugerdil, Lucas; Peyron, Odile; Ménot, Guillemette; Egamberdieva, Dilfuza; Alimov, Jakhongir; Leroy, Suzanne A G; Garnier, Eric; Nowak, Arkadiusz; Joannin, Sébastien (In: Dugerdil, L et al. (2025): Tajik-Uzbek Surface Data Base for modern pollen samples and vegetation plots: calibrations for functional diversity, climate and vegetation reconstructions in the past [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.979582, 2025)
This dataset details the plant functional traits (PFT) in the TUSDB based on pollen type. The PFTs are plant height (maximum plant height at plant maturity), leaf area (average surface of one side leaf), Leaf N (nitrogen content per leaf mass), seed mass (oven-dry mass of an average set of seeds), specific leaf area (SLA, the ratio between area and oven-dry mass of the leaf) and stem specific density (SSD, the ratio between stem dry mass and fresh volume of a stem section) and were extracted from the Tajikistan-Uzbekistan plant checklist. The values were aggregated for each pollen type of the TUSDB following two specific aggregation schemes: the fine aggregation (i.e. the higher level of pollen identification available) and the coarse aggregation (i.e. the most commonly used level of identification). All traits values have been z-scored. The "Growth form" here corresponds to the pollen class: Arboreal Pollen (AP), Non-Arboreal Pollen (NAP), Shrub Pollen (ShP) and Other (liana, aquatic, fern, ...).
Keywords: Arid Central Asia; climate reconstruction; plant functional traits; Pollen calibration; Pollen representativeness; Tajikistan; Uzbekistan; Vegetation plot